“É acompanhante ou usuária?” Implicações sobre a posição da família no atendimento a crianças e adolescentes em um Centro de Atenção Psicossocial da Infância e Adolescência - CAPSi - Souza Junior, João Camilo de (2016)
This study emerged and founded itself with the aim to analyze the position taken by the family – and the implications in this subjective area – in attending children and adolescents in a Childhood Psychosocial Care Center (CAPSi). A secondary goal has come up as the comprehension surrounding the institutional representation made about the family and the service offered to children, adolescents and relatives. For such, the historical perspective on the relation between the State (laws and institutions) and the family was resumed, and the understanding of how it was reconciled by the medical knowledge and attended the ideological and political means. The social and ideological transformations of the 20th century culminated in the need of change required by the Psychiatric Reform and the achievement of patients on the right to return home and to their families. This new situation, permeated by the attempt of building an assistance model in Mental Health, presented a peculiarity–the close relationship between family and Mental Health services. The observations and conversations at CAPSi that were the investigation objects in this research, intended to learn on the quotidian of families and the possible treatment alternatives that would take into account the family circumstances. Conceiving the status of the families in Mental Health services is a germinal matter yet to be adjusted among the active knowledge in the post-Reform devices. The discussion about the family bonds, anchored in the theoretical perspective of Binding Psychoanalysis brought up elementary concepts such as psychic heritage, denial pact, unconscious alliances, the familiar psychic set, among other. The concept of family organizer helped to think of the family trajectories and stablishes a sort of identity for the family, as well as interferes in the establishment of its boundaries. The family path within the institution, as well as the status they establish facing the institutional approach, reflect the ghosts and the organizers shared by the group-family. It follows that the family is an important protagonist to be considered in the current therapeutic and political processes and, thus, is key to welcome the family bonds for the alliances act over the affective destinations, as well as try to remain sealed from the proposed changes.